(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
In the contemporary global fashion system, branding has evolved from a purely commercial mechanism into a complex cultural and socio-economic phenomenon that shapes identity, values, and consumer behavior. Against the backdrop of globalization and visual homogenization, national ornament emerges as a critical resource for preserving cultural specificity while enhancing brand competitiveness. This article examines the actualization of national ornament in branding and the fashion industry through an interdisciplinary lens that integrates design theory, cultural studies, and economic analysis. The research aims to identify how traditional ornamental systems can be transformed into contemporary branding tools without losing their symbolic meaning and cultural integrity. Employing qualitative content analysis, comparative case studies, and design-based research methods, the study analyzes the functional, aesthetic, and economic roles of national ornament in fashion branding. The findings demonstrate that the strategic reinterpretation of national ornament strengthens brand identity, increases emotional consumer engagement, and contributes to sustainable and culturally responsible fashion practices. The article argues that the effective integration of national ornament requires a research-driven approach that balances innovation with cultural continuity, positioning ornament not as a decorative relic, but as an active generator of design value and socio-economic meaning.